2024
DOI: 10.1021/jacs.3c11334
|View full text |Cite
|
Sign up to set email alerts
|

Surface Extraction Process During Initial Oxidation of Pt(111): Effect of Hydrophilic/Hydrophobic Cations in Alkaline Media

Tomoaki Kumeda,
Kenshin Kondo,
Syunnosuke Tanaka
et al.

Abstract: The surface oxidation states of the metal electrodes affect the activity, selectivity, and stability of the electrocatalysts. Oxide formation and reduction on such electrodes must be comprehensively understood to achieve next-generation electrocatalysts with outstanding performance and stability. Herein, the initial electrochemical oxidation of Pt(111) in alkaline media containing hydrophilic and hydrophobic cations is investigated by X-ray crystal truncation rod (CTR) scattering, infrared (IR) spectroscopy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The organic cation is highly hydrophobic and cannot form favorable interactions with H 2 O, which forces adjacent H 2 O molecules to reorganize. In fact, it has been shown that the hydrophobicity of these cations effectively impedes the irreversible oxidation and surface roughening of Pt(111) electrocatalysts during oxide formation and reduction processes in alkaline media by inhibiting the formation of OH ads /O ads (H 2 O) on the surface . On the other hand, Na + establishes stronger interactions with H 2 O in its solvation shell than TBA + . , Different interactions with H 2 O could alter the state of the OH ads adlayer on Pt(111).…”
Section: Resultsmentioning
confidence: 99%
“…The organic cation is highly hydrophobic and cannot form favorable interactions with H 2 O, which forces adjacent H 2 O molecules to reorganize. In fact, it has been shown that the hydrophobicity of these cations effectively impedes the irreversible oxidation and surface roughening of Pt(111) electrocatalysts during oxide formation and reduction processes in alkaline media by inhibiting the formation of OH ads /O ads (H 2 O) on the surface . On the other hand, Na + establishes stronger interactions with H 2 O in its solvation shell than TBA + . , Different interactions with H 2 O could alter the state of the OH ads adlayer on Pt(111).…”
Section: Resultsmentioning
confidence: 99%